Capturing Complexity Complexities in Health Promotion Intervention Research: Conducting Critical Realist Evaluation realists Evaluation - Frohlich, Katherine L.; St-Arneault, Kate; St-Pierre, Mikael (Global Handbook of Health Promotion Research, Vol. 1: Mapping Health Promotion Research, 2022)
The circumstances in which everyday life takes place shapes people’s capacity to lead healthy lives. We posit that the traditional linear way of thinking about causes and consequences limits our ability to fully capture the complexity of the interaction between people and their contextual circumstances in the production of health. We view critical realism as particularly helpful in understanding how problems are generated by this interaction as well as understanding the fit and responsiveness of our interventions to situational contexts. Such a perspective requires systematically attempting to “unpack” how different settings are shaped by health promotion interventions and how this is experienced by people. Accessing and mobilising such knowledge also requires particular sets of methods that deviate from what is still often seen as the gold standard for designing and evaluating interventions. Critical realism therefore shifts the primary focus of health promotion research from questions about “if” interventions work to questions about “how”, “why” and “under what circumstances” they can work. By helping to capture complexity in health promotion intervention research, a critical realist perspective leads to the production of rigorous knowledge without having to succumb to concerns about standardisation.
Keywords: Healthy cities; Outdoor free-play; Participatory planning

“Opening Innovation” Across Layers of Practices: Developing an Integrative View of the Emergence of Digital Health - Dionne, Karl-Emanuel; Carlile, Paul (Managing Inter-organizational Collaborations: Process Views, 2019)
Innovation challenges are increasingly complex, cutting across distributed actors from different disciplines, organizations, and fields. Solving such challenges requires creating the capacities of opening up for innovation to access and develop a greater amount and variety of knowledge and resources. Perspectives on open source, open innovation, and interorganizational collaboration have explored such capacities, but from different origins and scopes of analysis. Our practice-based integrative framework of “opening innovation” helps highlight these differences and connect their relative strengths. Through a critical literature review paired with an analysis of different empirical cases from Hacking Health, a non-profit organization helping drive digital health innovation, the authors reveal the user-centric, firm-centric, and field-centric approaches to opening innovation that progressively connect a greater variety of actors and resources. The authors show how specific new relational practices they produce address the new relational dynamics these connections bring to accumulate more resources for innovation to keep progressing.
Keywords: Collaboration interorganisationnelle; Healthcare; Innovation ouverte; Open source

II. Regard sur le contrôle organisationnel de l’innovation sociale : réflexion contre-intuitive - Codello, Pénélope (GESS, 2018)
La gestion est-elle un mal ou un remède pour les entreprises sociales et solidaires ? Les entreprises sociales et solidaires sont-elles des modèles d’apprentissage pour la gestion ? Nous amènent-elles à penser la gestion autrement ? Cet ouvrage vise à dépasser les tabous liés à la gestion dans l’entreprise sociale et solidaire. Collectif de chercheurs en sciences humaines et sociales (académiques et/ou praticiens), notre ambition est de porter un regard critique sur la gestion des entreprises sociales et solidaires. Sur la base de l’étude de nombreux cas (mutuelles, associations, coopératives de consommateurs, banques coopératives, Scop, Scic, etc.), il s’agit de questionner et comprendre les dispositifs et les pratiques de gestion des entreprises sociales et solidaires. La réflexion des auteurs s’est construite autour des questionnements suivants : Que nous apprennent les entreprises sociales et solidaires sur la gestion des organisations ? Qu’ont-elles mis en œuvre de spécifique ? Existe-t-il déjà des « pépites » à observer, à essaimer issues de leurs pratiques de gestion ? Le phénomène d’isomorphisme avec les modèles d’entreprise capitaliste est-il si important ? Si oui, est-il un problème ? Pourquoi ? Et comment construire d’autres modes de gestion ? Quelles questions les organisations doivent-elles se poser pour dépasser les tensions inhérentes à l’hybridité entre économique, social ou solidaire ? Que doivent-elles inventer ? L’ouvrage se compose d’essais qui visent à défendre des points de vue sur des sujets récurrents et importants pour les entreprises sociales et solidaires. Ces derniers sont organisés en quatre thèmes : dépasser les tabous pour une gestion utile au projet social ou solidaire ; gestion pour et par la valeur sociale ; comment organiser durablement la gouvernance démocratique ; penser autrement la gestion des ressources humaines dans l’entreprise sociale et solidaire. Ces questions, nous l’espérons, feront sens et aideront tant dans la compréhension des phénomènes que dans la prise de décisions et la formation pour une gestion au service des entreprises sociales et solidaires.

Responsible Innovation in Business - Jarmai, Katharina; Tharani, Adele; Nwafor, Caroline (Responsible Innovation : Business Opportunities and Strategies for Implementation, 2020)
This chapter introduces responsible innovation in a business context. The first part explains the basic terms that constitute responsible innovation from a business perspective. The second part presents tangible business practices that operationalise responsible innovation and introduces two good practice examples that hint at the variety of ways in which responsible innovation can be implemented in companies.
Keywords: Innovation responsable; Responsible research and innovation

A Vision of Responsible Research and Innovation - Schomberg, Rene (Responsible Innovation: Managing the Responsible Emergence of Science and Innovation in Society, 2013)
I provide a vision and definition of Responsible Research and Innovation and propose a broad framework for its implementation under Research and Innovation schemes around the world. I make the case that RRI should be understood as a strategy of stakeholders to become mutual responsive to each other and anticipate research and innovation outcomes underpinning the "grand challenges" of our time for which they share > responsibility.> Research and Innovation processes need to become more responsive and adaptive to these grand challenges. This implies, among other, the introduction of broader foresight and impact assessments for new technologies beyond their anticipated market-benefits and risks. Social benefits of new technologies need to take into account widely shared public values. This implies a paradigm shift in innovation policy, moving away from an emphasis on key technologies towards issue and mission oriented policies. Background information can be found on: http://Renevonschomberg.wordpress.com

A Spotlight of Co-creation and Inclusiveness of Public Open Spaces - Šuklje Erjavec, Ina; Ruchinskaya, Tatiana (CyberParks – The Interface Between People, Places and Technology: New Approaches and Perspectives, 2019)
This chapter focuses on co-creation as the way to engage different stakeholders with everyday urban environments based on equality, diversity and social cohesion. It presents the relationship of co-creation and inclusiveness of public open spaces together with different aspects of co-creation related to issues of publicness and space. It discusses why and how co-creation must take into consideration the characteristics of the comprehensive spatial development processes. It suggests that co-creation is a wider concept than co-design and is a multistage process that contributes to inclusive public spaces, providing measures for social sustainability of place. This chapter argues that digital tools may help to overcome challenges of co-creation and provide an opinion on the contribution of digital technologies to the co-creation process by engaging people in the design, use and management of public spaces, providing new resources for interaction and users’ empowerment. For that it presents an overview of the possible contribution of digital technologies to support inclusiveness of the co-creation processes that is structured by typologies of digital tools and their possible interlinking with the steps of the co-creation process. To improve the understanding of such possibilities it critically addresses strengths and weaknesses of using digital tools for co-creation and inclusiveness and provides recommendations for their further development.
Keywords: Co-création; Inclusion; Outil numérique

Between Good Intentions and Enthusiastic Professors: The Missing Middle of University Social Innovation Structures in the Quadruple Helix - Benneworth, Paul; Cunha, Jorge; Cinar, Ridvan (Regional Helix Ecosystems and Sustainable Growth: The Interaction of Innovation, Entrepreneurship and Technology Transfer, 2020)
This chapter considers the role of universities in stimulating social innovation, and in particular the issue that despite possessing substantive knowledge that might be useful for stimulating social innovation, universities to date have not been widely engaged in social innovation activities in the context of Quadruple Helix developmental models. We explain this in terms of the institutional logics of engaged universities, in which entrepreneurial logics have emerged in recent decades, that frame the desirable forms of university-society engagement in terms of the economic benefits they bring. We ask whether institutional logics could explain this resistance of universities to social innovation. Drawing on two case studies of universities sincerely committed to supporting social innovation, we chart the effects of institutional logics on university-supported social innovation. We observe that there is a “missing middle” between enthusiastic managers and engaged professors, in which four factors serve to undermine social innovation activities becoming strategically important to HEIs. We conclude by noting that this missing middle also serves to segment the operation of Quadruple Helix relationships, thereby undermining university contributions to societal development more generally.
Keywords: Innovation sociale; Quadruple helix approach; Réservé UdeM; Rôle des universités; Université

Du modèle québécois à l’autoritarisme. La résilience des associations à l’épreuve - Lachapelle, René; Bourque, Denis (Du social business à l’économie solidaire, 2020)
Face à la conception technocratique et entrepreneuriale portée par les pouvoirs publics, une approche alternative de l’innovation sociale, plus populaire et moins visible, à travers l’exploration d’initiatives citoyennes. Prenant comme point de départ le constat d’une appropriation institutionnelle de l’innovation sociale, orientée vers la compétitivité et l’efficacité marchande des expériences de l’économie sociale et solidaire, l’ouvrage vise à la fois à apporter un regard critique sur cette conception de l’innovation sociale et à remettre en lumière des expérimentations citoyennes peu prises en compte par les pouvoirs publics. Il montre ainsi la nécessité d’un tournant épistémologique valorisant les dynamiques de coproduction des savoirs et des politiques entre acteurs, chercheurs et institutions.
Keywords: Associations; Concertation; Gestion axée sur les résultats; Innovation sociale; Philanthropie; Québec; Réservé UdeM; Santé; Éco-développement; Économie sociale; État

Les enjeux de la transition numérique et de l’innovation collaborative dans les mutations du travail et du management dans le secteur public - Zacklad, Manuel (Travailler dans les services publics : la nouvelle donne, 2020)
La transformation numérique et l’innovation collaborative ou les notions associées « d’intelligence collective », de « design thinking », « d’agilité » sont en passe de devenir les principaux concepts à la mode du management dans les organisations privées et publiques, au moins au sein des sièges et des directions centrales. Partant d’une description des spécificités des bouleversements introduits par la transition numérique et des technologies capacitantes qu’elle promeut, nous montrons comment les opérateurs sont parfois en demande de plus d’innovations numériques pour améliorer leurs conditions de travail et les services rendus au public, pour autant que celles-ci ne soient pas substitutives et excessivement rationalisantes. Les démarches d’innovation collaborative, soutenues par le haut management de manière parfois paradoxale, contribuent à faciliter ces mutations.
Keywords: Co-design; Collaboration; Innovation agile; Innovation collaborative; Intelligence collective; Numérique; Réservé UdeM; Secteur public

Good and Bad Innovation: What Theory and Practice Do We Need to Distinguish Them? - Mulgan, Geoff (Social Innovation: How Societies Find the Power to Change, 2019)
Technology is the answer, but what was the question? Introduction Many firms, charities and governments are in favour of more innovation, and like to side with the new against the old. But should they? A moment's reflection shows that it's not altogether coherent (whether intellectually, ethically or in terms of policy) to simply be in favour of innovation, whether that innovation is a product, a service or a social idea. Some innovations are unambiguously good (like penicillin or the telephone). Others are unambiguously bad (like concentration camps or nerve gas). Many are ambiguous. Pesticides kill parasites but also pollute the water supply. New surveillance technologies may increase workplace productivity but leave workers more stressed and unhappy. Smart missiles may be good for the nations deploying them and terrible for the ones on the receiving end.In finance, Paul Volcker, former head of the US Federal Reserve, said that the only good financial innovation he could think of was the automated teller machine. That was an exaggeration. But there is no doubt that many financial innovations destroyed more value than they created, even as they enriched their providers, and that regulators and policy makers failed to distinguish the good from the bad, with very costly results. In technology, too, a similar scepticism had emerged by the late 2010s, with digital social media described as the ‘new tobacco’, associated with harm rather than good, with addiction rather than help. Or, to take another example: when the US Central Intelligence Agency's venture capital arm, In-QTel, invested heavily in firms like Palantir, which then became contractors for the intelligence and military (a prime example of the ‘entrepreneurial state’), it was far from obvious how much this was good or bad for the world.The traditional justification for a capitalist market economy is that the net effects of market-led innovation leave behind far more winners than losers, and that markets are better able to pick technologies than bureaucracies or committees. But even if, overall, the patterns of change generate more winners than losers, there are likely to be some, perhaps many, cases where the opposite happens. It would be useful to know.
Keywords: Innovation; Innovation financière; Innovation sociale; Investissement; Réservé UdeM; États-Unis

Contexts of Co-creation: Designing with System Stakeholders - Jones, Peter (Systemic Design: Theory, Methods, and Practice, 2018)
The concept of co-creation includes a wide range of participatory practices for design and decision making with stakeholders and users. Generally co-creation refers to a style of design or business practice characterized by facilitated participation in orchestrated multi-stakeholder engagements, such as structured workshops and self-organizing modes of engagement. Co-creation envelopes a wide range of skilled social practices that can considerably inform and enhance the effectiveness of organizational development, collaboration, and positive group outcomes. New modes of co-creation have emerged, evolving from legacy forms of engagement such as participatory design and charrettes and newer forms such as collaboratories, generative design, sprints, and labs. Often sessions are structured by methods that recommend common steps or stages, as in design thinking workshops, and some are explicitly undirected and open. While practices abound, we find almost no research theorizing the effectiveness of these models compared to conventional structures of facilitation. As co-creation approaches have become central to systemic design, service design, and participatory design practices, a practice theory from which models might be selected and modified would offer value to practitioners and the literature. The framework that follows was evolved from and assessed by a practice theory of dialogic design. It is intended to guide the development of principles-based guidelines for co-creation practice, which might methodologically bridge the wide epistemological variances that remain unacknowledged in stakeholder co-creation practice.
Keywords: Co-création; Collaboration; Japon; Recommandations; Réservé UdeM

Pour un questionnement critique de l’innovation sociale - Juan, Maïté; Laville, Jean-Louis (Du social business à l’économie solidaire : Critique de l’innovation sociale, 2020)
L’innovation sociale est largement considérée comme vertueuse. Cependant, le consensus qui semble régner en la matière vient de ce que les représentations et les pratiques englobées sous ce terme recouvrent un faisceau très diversifié d’approches et de réalités. Cette polysémie permet à de nombreux auteurs de se ranger sous une même bannière alors qu’ils ont des références et des orientations distinctes, voire divergentes. L’éloge unanime de l’innovation sociale ne saurait donc faire illusion. À cet égard, un travail introductif autour de l’innovation sociale a mis en évidence deux acceptions contrastées. La première version, qui peut être qualifiée de faible, aménage le système existant, insiste sur l’importance de l’épreuve marchande et valorise l’entreprise privée dans sa capacité à trouver de nouvelles solutions aux problèmes de société. La seconde version, qui peut être désignée comme forte, affiche une visée transformatrice ; elle prône, en réaction à la démesure du capitalisme marchand, une articulation inédite entre pouvoirs publics et société civile pour répondre aux défis écologiques et sociaux. La première se contente d’une amélioration du modèle économique dominant, l’innovation s’inscrivant dans une perspective réparatrice et fonctionnelle, tandis que la seconde a pour caractéristique un questionnement critique de ce modèle, et a pour horizon une démocratisation de la société.
Keywords: Innovation sociale; Réservé UdeM; Transformations; social business; Économie sociale; Économie solidaire

Social Science and Intelligence Design - Mulgan, Geoff (Social Innovation: How Societies Find the Power to Change, 2019)
In this chapter I turn to how social science can be adapted to the challenges and tools of the 2020s, becoming more data driven, more experimental and fuelled by more dynamic feedback between theory and practice. Social science at its grandest is the way societies understand themselves: why they cohere or fall apart; why some grow and others shrink; why some care and others hate; how big structural forces explain the apparently special facts of our own biographies. It observes but also shapes action, and then learns from those actions.Starting with the idea of social science as collective selfknowledge, I describe how new approaches to intelligence of all kinds can help to reinvigorate it. I begin with data and computational social science and then move on to cover the idea of social R&D and experimentation, new ways for universities to link into practice, including social science parks, accelerators tied to social goals, challenge-based methods and social labs of all kinds, before concluding with the core argument: an account of how social science can engage with the emerging field of intelligence design. This is, I hope, a plausible and desirable direction of travel.The rise of data-driven and computational social ScienceWe are all familiar with the extraordinary explosion of new ways to observe social phenomena, which are bound to change how we ask social questions and how we answer them. Each of us leaves a data trail of whom we talk to, what we eat and where we go. It's easier than ever to survey people, to spot patterns, to scrape the web, to pick up data from sensors or to interpret moods from facial expressions. It's easier than ever to gather perceptions and emotions as well as material facts – for example, through sentiment analysis of public debates. And it's easier than ever for organisations to practise social science – whether it's investment organisations analysing market patterns, human resources departments using behavioural science or local authorities using ethnography.These tools are not monopolised by professional social scientists. In cities, for example, offices of data analytics link multiple data sets and governments use data to feed tools using AI – like Predpol or HART – to predict who is most likely to go to hospital or end up in prison.
Keywords: Changement social; Recherche; Réservé UdeM; Université

Know Your Impact (and in Praise of Better Borrowing) - Mulgan Geoff (Social Innovation: How Societies Find the Power to Change, 2019)
This chapter is about evidence and whether we can, or should, know our impact, the effect we have in the world. It addresses the difficulties as well as the possibilities of evidence for innovators and politicians, civil servants and head teachers, charities and doctors. I also touch on the question at the level of daily life, the moral question of whether we help those around us to be healthier, happier and more prosperous. Knowing our own impacts is, I argue, as much a moral prerogative as the traditional philosophical injunction of knowing ourselves.The enlightenment storyMany of us imbibed from an early age what can be called the enlightenment story. In this story new knowledge is steadily accumulated, mainly in universities and from academic journals. Theories are invented, tested, refuted and then improved. Scepticism helps to refine them and, as Wittgenstein wrote, the child first learns belief and only then learns doubt. You could say that at school we learn knowledge, and then at university we learn to question that knowledge.Belief is strengthened precisely because it has already been knocked down. And so, accumulating knowledge shows that this medicine, that economic policy or this teaching method works and many others don’t. The successful method then spreads, because when you design a better mousetrap the world beats a path to your door. It spreads because people are rational and want to do better and are persuaded by evidence. And so, the world progresses. Light replaces darkness. Effective solutions displace failed ones.It's easy to mock the enlightenment story. The sociologists of science have shown a much messier pattern of change – full of barriers, wilful resistance and peer pressure. But the old enlightenment story contains a good deal of truth and is preferable to the alternatives. Because of intense pressures to act on evidence, and habits of doubt among maintenance staff and engineers, aircraft do not drop out of the sky. Smoking made the slow progress from evidence of harm, through taxes and warnings to full-scale bans, and millions of lives were saved.Experimental methods have been used for many decades.
Keywords: Mesure d'impact; Réservé UdeM

The Evolution of Measures That Matter: How Do We Know If Social Innovation is Working? - Mulgan, Geoff (Social Innovation: How Societies Find the Power to Change, 2019)
In the kingdom of ends everything has either a price or a dignity. What has a price can be replaced by something else as its equivalent; what on the other hand is raised above all price and therefore admits of no equivalent has a dignity.One of the fascinating features of the history of science is how often new ways of seeing preceded new insights. The achromatic-lens microscope in the early 19th century paved the way for germ theory, and X-ray crystallography in the early 20th century played a vital role in the later discovery of the structure of DNA. In the same way flows of data – for example, about how people move around a city, or how blood cells change – can prompt new insights.But how important is measurement to social change? Many people are attracted to metrics and indices of all kinds. But, as my colleague Mark Moore used to warn, ‘do you really think the leaders of the Civil Rights Movement were counting the placards or measuring the decibels of their cries for human rights?’ In social change, as in our own daily lives, measurement often feels inappropriate for the things that matter most.This chapter examines some of the history of social observation as a tool for public policy, social innovation and social change, and I suggest where it might lead in the future. Without some means of measurement, it can be hard to know if a social innovation is good. It may feel good to the beneficiaries – but still be less effective than an alternative. Or it may work well for one group but not another. And, even if it may not be appropriate to measure the passions of movements, once these ideas become part of the mainstream, and are transformed into the cool logic of laws, regulations and programmes, measurements do start to matter a lot, as the Civil Rights Movement discovered.A short history of measurementFor centuries, governments have sought to map and measure social phenomena in order to better exercise control over them. In the modern era these attempts can be traced back to figures like Sir William Petty in England and the cameralists in Prussia.
Keywords: Mesure d'impact; Réservé UdeM

Innovations in Multistakeholder Partnerships for Sustainable Development: Fostering State–University–Community Nexus - Shaban, Abdul; Narnaware, Prashant B. (People-Centered Social Innovation, 2019)
This chapter shows that there is a possibility of fostering an enabling and innovative multistakeholder partnership for creating sustainable impact and transformative change with local communities. It argues that the collaborative efforts among district administration, educational institutions and civil society groups in supporting innovation and entrepreneurship can play an extremely important role in livelihood security and empowerment of marginalized sections. The chapter outlines the transformation of a marginalized and underdeveloped district of India. It presents a background of the district with a focus on farmers’ distress and discusses the mode of organization of elites and marginalized peoples under welfare and neoliberal regimes. The chapter also outlines the impact that state–university engagement on the communities. The neoliberal regime made the elite-based cooperatives ineffective, as they came under mismanagement and overexploitation by those in power. Neoliberal reform introduced a new vulnerability among Indian farmers, especially in certain states, such as Maharashtra.
Keywords: Asie; Réservé UdeM; Rôle des universités

Social Entrepreneurship in an Era of Disruption: Converging Social Change and Sustainability Through Big Data Analysis in a Post-COVID World - Nag, Manmeet Bali (Entrepreneurship and Big Data, 2021)
The world is witnessing an unprecedented disruption due to the COVID-19 pandemic in almost all spheres of socio-economic activity. This black swan moment is unprecedented since the advent of the Industrial Revolution. Simultaneously, there is a shift towards effective use of data and technology. There is an exponential increase in the quantum of data collected and has subsequently necessitated a paradigm shift in the functioning of Industry 4.0. Data intelligence, data science, artificial intelligence, machine learning, and deep assimilation of nuanced knowledge revolutionize business and society worldwide. This heralds a potential transition towards data-intensive economies, governments, industrial and social sectors. The accelerated pace of data processing, data intelligence, and analytics encompasses business intelligence, data sciences and machine learning. The spectrum of such upheavals and associated technological transitions is a watershed moment and impacts business and social transformations. In the paper on the role of data in the social realm (Technology as a catalyst for sustainable social business: Advancing the research agenda, 2019). Ashraf et al. opine that “Despite its immense potentials as a sustainable and innovative means to solve specific social problems, the basic concept of the social business model remains unclear to many”. In recent times there has been an inconsistent approach towards social business research. Subsequently, the contemporary business scenario is yet to optimally capitalize on the advantages of the Social Business concept and address the divergent socio-economic and ecological issues worldwide, with profits intact. This should in no way dilute profit maximization for optimizing socio-economic benefits for value creation and sustainability. “Although the social enterprise is often considered to have positive future potential, it is currently underdeveloped” (Bell, 2003). Therefore, social entrepreneurship should generate and ensure nuanced and effective innovations, addressing underserved needs. In contemporary times, tools harnessing Big Data are becoming widely applied, leading to a huge reservoir of untapped diverse data. This subsequently creates an immense opportunity to accelerate the use of Big Data towards social good and sustainability. Though this is a recent trend, it indeed holds promise in the post-COVID world that would be privy to unprecedented socio-economic upheavals and an increased need to address issues of humankind for greater global welfare. In the recent past, diverse data sets have created large-scale solutions in diverse spheres ranging from weather forecasts to airline tickets. Insightful correlations and Big Data go hand in hand and hold the key to several complicated pressing social issues. Therefore, a new crop of social entrepreneurs in public health, social welfare, and humanitarian relief would surely emerge by default. Therefore, it is all the more relevant to make sense of a deluge of Big Data towards alleviating a disease, ecological imbalance, war, and most importantly, the patterns to cope with the disease and its aftermath. This chapter proposes anticipating and predicting the immense possibilities of optimizing Big Data and digitization as key critical drivers of empirical simulation and troubleshooting. Good governance, inclusive society, elimination of corruption, and streamlining policy measures would emerge as default collectives of such social entrepreneurial ventures. The chapter would draw inferences from such models of socially inclined data analytics by data scientists, leading to relevant social models of significance. Implications of the chapter would be to assuage the fault lines, draw inferences from the past, and delve into the plausibility and relevance of Big Data to replicate and innovate socially relevant models to map bigger social issues. This, of course, should have embedded benchmarks of equality, ethics, and empowerment while processing Big Data for a greater social good in a post-COVID world gaping at us.
Keywords: Big Data; Entrepreneuriat; Réservé UdeM; Social entrepreneurship

Social Entrepreneurship - Sumbly, Sangeeta (Entrepreneurship and Big Data, 2021)
Social entrepreneurship is today an imperative across the world. The scarcity of resources, the needs of the growing population, and the growing burden on the environment have made people realize a need for organizations that can be profitable while bringing positive change in society and the environment. Sustainable, out-of-the-box solutions are required for solving social challenges. The onus of providing these solutions are often taken by aspiring entrepreneurs, who see opportunity in the challenges and are willing to take risks to create innovative and effective solutions for society’s benefit. The chapter elucidates the meaning of social entrepreneurship, the difference between commercial and social entrepreneurship, the models of social enterprises in practice, and the recommended methodology to evaluate social impact. The chapter features international case studies (through secondary research) and cases about social entrepreneurs who have dramatically improved the lives of people while being financially sustainable – an organization like SELCO Solar Lights Private Ltd, ARMAAN, Yellow Leaf and Arvind Eye Hospital, and many others have provided solutions for the economically weaker section of society. Many of these new-age social entrepreneurs use Big Data and artificial intelligence to ensure that their initiatives create greater social change. Some of these initiatives are highlighted in the chapter.
Keywords: Big Data; Entrepreneuriat; Réservé UdeM; Social entrepreneurship; social

Philanthropy and Innovation - Dodgson, Mark; Gann, David (Philanthropy, Innovation and Entrepreneurship: An Introduction, 2020)
This chapter examines the close relationships between philanthropy and innovation. A case study of philanthropy improving eyesight in Africa is provided. The crucial impact of philanthropy on science and universities is discussed. A case study of how philanthropy fundamentally changed Queensland University is provided. The intimate relationship between philanthropy and the arts is explored. A case study is provided of the impact of philanthropy on a major arts institution. The connections between philanthropy and social and humanitarian innovation is described.
Keywords: Australie; Réservé UdeM

Toward the Practice of Social Innovation for the Common Good: An Integration of “Teaching-Research-Service” - Han, I.; Hou, Sheng-Tsung (Social Innovation and Business in Taiwan, 2016)
“Many suppliers and users of social research are dissatisfied, the former because they are not listened to, the latter because they do not hear much they want to listen to” (Lindblom & Cohen, 1979: 1). As mentioned in Chapter 1 of this book, the recent events of global financial crisis and a series of Occupy Wall Street protests have raised reflections of business management education on MBA trainings. The question of whether management research and education can be a facilitator toward events that would eventually destroy the world economy or a facilitator toward achieving social value and human glory has been raised with those reflections. MBA graduates should not be used as profiting tools for big corporations anymore. Moreover, the separation between management theory and industry practice has, for a long time, caused a dilemma with regard to the difficulties inherent in dialogue between academia and industry. There have been urgent calls to embody management research into applicable industry knowledge in order to minimize the gap in between the two (Anderson, Herriot, & Hodgkinson, 2001; Rynes, Bartunek, & Daft, 2001; Van de Yen & Johnson, 2006).
Keywords: Asie; Réservé UdeM

LES MODES D’INNOVATION SOCIALE ET DE GOUVERNANCE - Castro-Spila, Javier; Unceta, Alfonso (La transformation sociale par l'innovation sociale, 2016)
La relation entre l’innovation sociale et la gouvernance n’est pas suffisamment explorée dans la littérature scientifique. Les analyses que l’on trouve sur ce sujet se rapportent principalement à la relation entre l’administration publique, la participation citoyenne, le changement social et les nouvelles formes de gouvernance (Lévesque, 2012 ; Moulaertet al., 2007 ; Novy, Hamme et Leubolt, 2009). Dans ces approches, l’innovation sociale est abordée comme le rapport entre les relations sociales et la gouvernance. Ainsi, cette perspective cherche plutôt à comprendre comment certains groupes sociaux développent leurs capacités sociopolitiques pour garantir leur accès aux ressources qui permettent de répondre

Chapitre 5. Entrepreneuriat social - Fayolle, Alain (Entrepreneuriat : Théories et pratiques, Applications pour apprendre à entreprendre, 2017)
Keywords: Réservé UdeM

Définition et dimensions de la co-construction - Foudriat, Michel (La co-construction : une alternative managériale, 2019)
La co-construction est un processus par lequel des acteurs différents confrontent leurs points de vue et s’engagent dans une transformation de ceux-ci jusqu’au moment où ils s’accordent sur des traductions qu’ils ne perçoivent plus comme incompatibles. Ce moment particulier est celui où ils pensent avoir défini un « monde commun » qui va fonder leur compromis ; ils pourront alors poursuivre leur coopération afin de construire un projet d’action commun et réfléchir ensemble à sa mise en œuvre. La notion de co-construction s’est largement diffusée dans le monde académique et non académique. Cependant, sa définition reste encore aujourd’hui incertaine et fait l’objet de propositions dans la littérature grise des dossiers, finalisée par des institutions (certains conseils généraux, entre autres) ou des cabinets conseil. Pratiquement aucun dictionnaire de sociologie ou de sciences humaines ne la définit à l’exception du Dictionnaire de la participation . « Le terme co-construction est devenu depuis quelques années très en vue. Il se retrouve dans beaucoup d’articles et livres à portée académique. L’univers professionnel n’en est pas moins en reste où cette approche de gestion semble l’un des moyens pour pérenniser la performance des organisations. Néanmoins, lorsque l’on s’y attarde un peu plus en profondeur, on constate qu’il est davantage cité que conceptualisé. Très peu d’auteurs s’y sont réellement attardés ». C’est une notion ambiguë et la proximité avec des notions voisines plus académiques comme la coopération n’est sans doute pas une condition facilitatrice pour une explicitation de ses dimensions propres…
Keywords: Co-construction; Définition; Réservé UdeM

L’innovation sociale au Québec : un système d’innovation fondé sur la concertation - Klein, Juan-Luis; Fontan, Jean-Marc; Harrisson, Denis; Lévesque, Benoît (L'innovation sociale, 2014)
Des politiques en faveur de l’innovation sociale se mettent en place à différents niveaux (local, régional, national, européen). Pour autant et malgré l’augmentation exponentielle des références dans la littérature internationale, peut-on s’accorder sur une vision de l’innovation sociale ? Pour les auteurs réunis ici, elle ne constitue ni une recette ni la simple diffusion de ce qu’on appelle des « bonnes pratiques », qui opèreraient dans des systèmes économiques et sociaux inchangés. en effet, les capacités d’initiative de la société civile exigent des changements dans les cadres institutionnels pour construire un nouveau modèle de société inclusif, solidaire et écologique. À partir de l’expérience et des acquis de trois équipes de recherche qui y réfléchissent depuis plus de vingt ans, cet ouvrage alimente le débat théorique sur l’innovation sociale. Il explique aussi pourquoi la thématique est apparue dans une période de mutations contemporaines et montre l’importance pratique qu’elle peut revêtir à travers des exemples de territoires comme de secteurs.
Keywords: Idéation, dialogue et maillage; Québec; Étude de cas

Indicators for Measuring Social Innovation - Kleverbeck, Maria; Krlev, Gorgi; Mildenberger, Georg; Strambach, Simone; Thurmann, Jan-Frederik; Terstriep, Judith; Wloka, Laura (2019)
Addressing a largely underexplored research field, this article centres on the development of indicators to grasp social innovation at different analytical levels: organisational innovativeness, regional innovation capacity, and resonance, to position social innovation in the broader field of innovation.

Les initiatives locales et l’évaluation habilitante : proposition d’une méthode proactive appuyée sur la reconstitution historique - Fontan, Jean-Marc; Klein, Juan-Luis; Champagne, Christine (2014)
Réunissant les contributions d’une trentaine de chercheurs provenant de disciplines variées (géographie, économie, sociologie, démographie, science politique, anthropologie, sciences administratives, ethnologie), cet ouvrage représente le fruit de la plus importante réflexion collective à propos des méthodologies de recherche pour saisir les territoires, qu’ils soient urbains, régionaux, ruraux, métropolitains ou périphériques. Plusieurs questions territoriales contemporaines ou plus anciennes y sont traitées, telles que le management, les disparités, l’attractivité, l’identité, l’innovation, la régulation, le capital social, l’appropriation, la centralité, l’acceptabilité sociale, les parties prenantes, la revitalisation et l’accessibilité. Le souci de transversalité s’inscrit au cœur des approches méthodologiques complémentaires et convergentes qui sont offertes. Non seulement l’ouvrage éclaire les lecteurs sur les différentes méthodes utilisées par les chercheurs pour comprendre les territoires, mais il leur donne aussi des outils concrets pour élaborer une problématique, proposer un cadre conceptuel, soulever une question pertinente, définir des indicateurs, classifier des attributs, isoler des causes, mesurer des effets et vérifier des hypothèses. En conséquence, il devient une référence incontournable pour lancer de nouvelles recherches scientifiques sur l’objet que sont les territoires qui composent les nations.

Définition et dimensions de la co-construction - Foudriat, Michel (La co-construction : une alternative managériale, 2019)
La co-construction est un processus par lequel des acteurs différents confrontent leurs points de vue et s’engagent dans une transformation de ceux-ci jusqu’au moment où ils s’accordent sur des traductions qu’ils ne perçoivent plus comme incompatibles. Ce moment particulier est celui où ils pensent avoir défini un « monde commun » qui va fonder leur compromis ; ils pourront alors poursuivre leur coopération afin de construire un projet d’action commun et réfléchir ensemble à sa mise en œuvre. La notion de co-construction s’est largement diffusée dans le monde académique et non académique. Cependant, sa définition reste encore aujourd’hui incertaine et fait l’objet de propositions dans la littérature grise des dossiers, finalisée par des institutions (certains conseils généraux, entre autres) ou des cabinets conseil. Pratiquement aucun dictionnaire de sociologie ou de sciences humaines ne la définit à l’exception du Dictionnaire de la participation . « Le terme co-construction est devenu depuis quelques années très en vue. Il se retrouve dans beaucoup d’articles et livres à portée académique. L’univers professionnel n’en est pas moins en reste où cette approche de gestion semble l’un des moyens pour pérenniser la performance des organisations. Néanmoins, lorsque l’on s’y attarde un peu plus en profondeur, on constate qu’il est davantage cité que conceptualisé. Très peu d’auteurs s’y sont réellement attardés ». C’est une notion ambiguë et la proximité avec des notions voisines plus académiques comme la coopération n’est sans doute pas une condition facilitatrice pour une explicitation de ses dimensions propres…
Keywords: Co-construction; Définition; Réservé UdeM

Social Science and Intelligence Design - Mulgan, Geoff (Social Innovation: How Societies Find the Power to Change, 2019)
In this chapter I turn to how social science can be adapted to the challenges and tools of the 2020s, becoming more data driven, more experimental and fuelled by more dynamic feedback between theory and practice. Social science at its grandest is the way societies understand themselves: why they cohere or fall apart; why some grow and others shrink; why some care and others hate; how big structural forces explain the apparently special facts of our own biographies. It observes but also shapes action, and then learns from those actions.Starting with the idea of social science as collective selfknowledge, I describe how new approaches to intelligence of all kinds can help to reinvigorate it. I begin with data and computational social science and then move on to cover the idea of social R&D and experimentation, new ways for universities to link into practice, including social science parks, accelerators tied to social goals, challenge-based methods and social labs of all kinds, before concluding with the core argument: an account of how social science can engage with the emerging field of intelligence design. This is, I hope, a plausible and desirable direction of travel.The rise of data-driven and computational social ScienceWe are all familiar with the extraordinary explosion of new ways to observe social phenomena, which are bound to change how we ask social questions and how we answer them. Each of us leaves a data trail of whom we talk to, what we eat and where we go. It's easier than ever to survey people, to spot patterns, to scrape the web, to pick up data from sensors or to interpret moods from facial expressions. It's easier than ever to gather perceptions and emotions as well as material facts – for example, through sentiment analysis of public debates. And it's easier than ever for organisations to practise social science – whether it's investment organisations analysing market patterns, human resources departments using behavioural science or local authorities using ethnography.These tools are not monopolised by professional social scientists. In cities, for example, offices of data analytics link multiple data sets and governments use data to feed tools using AI – like Predpol or HART – to predict who is most likely to go to hospital or end up in prison.
Keywords: Changement social; Recherche; Réservé UdeM; Université

Between Good Intentions and Enthusiastic Professors: The Missing Middle of University Social Innovation Structures in the Quadruple Helix - Benneworth, Paul; Cunha, Jorge; Cinar, Ridvan (Regional Helix Ecosystems and Sustainable Growth: The Interaction of Innovation, Entrepreneurship and Technology Transfer, 2020)
This chapter considers the role of universities in stimulating social innovation, and in particular the issue that despite possessing substantive knowledge that might be useful for stimulating social innovation, universities to date have not been widely engaged in social innovation activities in the context of Quadruple Helix developmental models. We explain this in terms of the institutional logics of engaged universities, in which entrepreneurial logics have emerged in recent decades, that frame the desirable forms of university-society engagement in terms of the economic benefits they bring. We ask whether institutional logics could explain this resistance of universities to social innovation. Drawing on two case studies of universities sincerely committed to supporting social innovation, we chart the effects of institutional logics on university-supported social innovation. We observe that there is a “missing middle” between enthusiastic managers and engaged professors, in which four factors serve to undermine social innovation activities becoming strategically important to HEIs. We conclude by noting that this missing middle also serves to segment the operation of Quadruple Helix relationships, thereby undermining university contributions to societal development more generally.
Keywords: Innovation sociale; Quadruple helix approach; Réservé UdeM; Rôle des universités; Université

Pour un questionnement critique de l’innovation sociale - Juan, Maïté; Laville, Jean-Louis (Du social business à l’économie solidaire : Critique de l’innovation sociale, 2020)
L’innovation sociale est largement considérée comme vertueuse. Cependant, le consensus qui semble régner en la matière vient de ce que les représentations et les pratiques englobées sous ce terme recouvrent un faisceau très diversifié d’approches et de réalités. Cette polysémie permet à de nombreux auteurs de se ranger sous une même bannière alors qu’ils ont des références et des orientations distinctes, voire divergentes. L’éloge unanime de l’innovation sociale ne saurait donc faire illusion. À cet égard, un travail introductif autour de l’innovation sociale a mis en évidence deux acceptions contrastées. La première version, qui peut être qualifiée de faible, aménage le système existant, insiste sur l’importance de l’épreuve marchande et valorise l’entreprise privée dans sa capacité à trouver de nouvelles solutions aux problèmes de société. La seconde version, qui peut être désignée comme forte, affiche une visée transformatrice ; elle prône, en réaction à la démesure du capitalisme marchand, une articulation inédite entre pouvoirs publics et société civile pour répondre aux défis écologiques et sociaux. La première se contente d’une amélioration du modèle économique dominant, l’innovation s’inscrivant dans une perspective réparatrice et fonctionnelle, tandis que la seconde a pour caractéristique un questionnement critique de ce modèle, et a pour horizon une démocratisation de la société.
Keywords: Innovation sociale; Réservé UdeM; Transformations; social business; Économie sociale; Économie solidaire

Du modèle québécois à l’autoritarisme. La résilience des associations à l’épreuve - Lachapelle, René; Bourque, Denis (Du social business à l’économie solidaire, 2020)
Face à la conception technocratique et entrepreneuriale portée par les pouvoirs publics, une approche alternative de l’innovation sociale, plus populaire et moins visible, à travers l’exploration d’initiatives citoyennes. Prenant comme point de départ le constat d’une appropriation institutionnelle de l’innovation sociale, orientée vers la compétitivité et l’efficacité marchande des expériences de l’économie sociale et solidaire, l’ouvrage vise à la fois à apporter un regard critique sur cette conception de l’innovation sociale et à remettre en lumière des expérimentations citoyennes peu prises en compte par les pouvoirs publics. Il montre ainsi la nécessité d’un tournant épistémologique valorisant les dynamiques de coproduction des savoirs et des politiques entre acteurs, chercheurs et institutions.
Keywords: Associations; Concertation; Gestion axée sur les résultats; Innovation sociale; Philanthropie; Québec; Réservé UdeM; Santé; Éco-développement; Économie sociale; État

Good and Bad Innovation: What Theory and Practice Do We Need to Distinguish Them? - Mulgan, Geoff (Social Innovation: How Societies Find the Power to Change, 2019)
Technology is the answer, but what was the question? Introduction Many firms, charities and governments are in favour of more innovation, and like to side with the new against the old. But should they? A moment's reflection shows that it's not altogether coherent (whether intellectually, ethically or in terms of policy) to simply be in favour of innovation, whether that innovation is a product, a service or a social idea. Some innovations are unambiguously good (like penicillin or the telephone). Others are unambiguously bad (like concentration camps or nerve gas). Many are ambiguous. Pesticides kill parasites but also pollute the water supply. New surveillance technologies may increase workplace productivity but leave workers more stressed and unhappy. Smart missiles may be good for the nations deploying them and terrible for the ones on the receiving end.In finance, Paul Volcker, former head of the US Federal Reserve, said that the only good financial innovation he could think of was the automated teller machine. That was an exaggeration. But there is no doubt that many financial innovations destroyed more value than they created, even as they enriched their providers, and that regulators and policy makers failed to distinguish the good from the bad, with very costly results. In technology, too, a similar scepticism had emerged by the late 2010s, with digital social media described as the ‘new tobacco’, associated with harm rather than good, with addiction rather than help. Or, to take another example: when the US Central Intelligence Agency's venture capital arm, In-QTel, invested heavily in firms like Palantir, which then became contractors for the intelligence and military (a prime example of the ‘entrepreneurial state’), it was far from obvious how much this was good or bad for the world.The traditional justification for a capitalist market economy is that the net effects of market-led innovation leave behind far more winners than losers, and that markets are better able to pick technologies than bureaucracies or committees. But even if, overall, the patterns of change generate more winners than losers, there are likely to be some, perhaps many, cases where the opposite happens. It would be useful to know.
Keywords: Innovation; Innovation financière; Innovation sociale; Investissement; Réservé UdeM; États-Unis

Les enjeux de la transition numérique et de l’innovation collaborative dans les mutations du travail et du management dans le secteur public - Zacklad, Manuel (Travailler dans les services publics : la nouvelle donne, 2020)
La transformation numérique et l’innovation collaborative ou les notions associées « d’intelligence collective », de « design thinking », « d’agilité » sont en passe de devenir les principaux concepts à la mode du management dans les organisations privées et publiques, au moins au sein des sièges et des directions centrales. Partant d’une description des spécificités des bouleversements introduits par la transition numérique et des technologies capacitantes qu’elle promeut, nous montrons comment les opérateurs sont parfois en demande de plus d’innovations numériques pour améliorer leurs conditions de travail et les services rendus au public, pour autant que celles-ci ne soient pas substitutives et excessivement rationalisantes. Les démarches d’innovation collaborative, soutenues par le haut management de manière parfois paradoxale, contribuent à faciliter ces mutations.
Keywords: Co-design; Collaboration; Innovation agile; Innovation collaborative; Intelligence collective; Numérique; Réservé UdeM; Secteur public

Contexts of Co-creation: Designing with System Stakeholders - Jones, Peter (Systemic Design: Theory, Methods, and Practice, 2018)
The concept of co-creation includes a wide range of participatory practices for design and decision making with stakeholders and users. Generally co-creation refers to a style of design or business practice characterized by facilitated participation in orchestrated multi-stakeholder engagements, such as structured workshops and self-organizing modes of engagement. Co-creation envelopes a wide range of skilled social practices that can considerably inform and enhance the effectiveness of organizational development, collaboration, and positive group outcomes. New modes of co-creation have emerged, evolving from legacy forms of engagement such as participatory design and charrettes and newer forms such as collaboratories, generative design, sprints, and labs. Often sessions are structured by methods that recommend common steps or stages, as in design thinking workshops, and some are explicitly undirected and open. While practices abound, we find almost no research theorizing the effectiveness of these models compared to conventional structures of facilitation. As co-creation approaches have become central to systemic design, service design, and participatory design practices, a practice theory from which models might be selected and modified would offer value to practitioners and the literature. The framework that follows was evolved from and assessed by a practice theory of dialogic design. It is intended to guide the development of principles-based guidelines for co-creation practice, which might methodologically bridge the wide epistemological variances that remain unacknowledged in stakeholder co-creation practice.
Keywords: Co-création; Collaboration; Idéation, dialogue et maillage; Japon; Réservé UdeM

Why Do Publicly Funded Firms Find the University More Useful to Innovate Than Others? Can We Accomplish the RIS3 Target? - Costa, Joana (Regional Helix Ecosystems and Sustainable Growth: The Interaction of Innovation, Entrepreneurship and Technology Transfer, 2020)
The failure of the deterritorialised innovation policy addressing the regions based on the “one-size-fits-all” policymaking made the Research and Innovation Strategies for Smart Specialisation (RIS3) become the Holy Grail of the European cohesion. This policy strategy is part of a multilevel framework, which encompasses national and regional vectors harmonising transversal strategies and combining different aspects to generate a consistent policy mix. This growth strategy will reinforce the existence of an innovative and knowledge-based society, which aims to raise welfare, promote responsible practices, modernise economic activity and spread prosperity.Sustainable growth will optimise the use of resources, boost the efficiency levels, generate competitiveness and respect the environment. Inclusive growth will promote social and territorial cohesion which is sought after in the convergence policy, which has slowed down the pace after the financial crisis.The development of regional competitive advantages will rely on the establishment of relevant linkages between the Academia and the private institutions in knowledge creation and transfer. In this vein, the University is expected to play a central role, facing important challenges and requiring transformations, mostly in the case of less favoured regions.Productivity raise, construction of comparative advantages, market consolidation and profit maximisation, required to avoid the obsolescence of firms, will rely in the prosecution of innovative activities. Despite being risky, these activities are sought by firms as a source of economic performance increase, being the building blocks of a profit maximisation strategy. The velocity at which innovation occurs will differ among industrial sectors due to their singularities along with other firm structural characteristics, still, those who perform innovative activities are more prone to achieve higher standards of turnover growth and profits. The organisational competences concerning human capital, knowledge absorption, accumulation and diffusion will enhance the innovation capabilities, thus generating advantages. In this path, Universities will be determinant as they may leverage the success of the entrepreneurial innovativeness throughout the provision of relevant knowledge, productive techniques and methods. Absorbing, transforming and exploiting the general knowledge provided by the University will be the firms’ incumbency which will reflect the speed and the success of the individual’s innovative performance. Considering the reinforced role of the Academia as a knowledge producer and therefore inside the innovation process, the existence of incipient connections with firms will be unbearable.What enables and hinders University-firm linkages is, so far, overlooked in the literature demanding for the comprehensive analysis, in particular the causes of its failure, and the accurate policy mix that overcome the situation is vital for a successful RIS3.The singularities of this policy framework require redirection of the tools and actions to be taken such as incentives, grants, loans and subsidisation strategies. Empirical results shed light to the significant difference observed in the classification of the University as a source of information for innovation between public monies recipients and other firms. Among public funding beneficiaries, the Academia is an important source of knowledge to draw upon; conversely, for the other firms, it seems of poor importance the knowledge conveyed in the contact. In general, firms fail to consider the University as a relevant source of information for innovation, which seems to be incompatible with the establishment of smart specialisation strategies.These unexplored connections, which pledge the success of the present innovation policy, and reinforce the importance of its appraisal to fully understand the determinants of University-firm linkages and its connection to public subsidisation, encompassing the identification of the most effective beneficiaries. The econometric estimations, relying on the CIS, were run considering a panel of firms operating in Portugal, which provides the empirical evidence for a moderate innovation milieu which is poorly done so far as most of the studies focus on innovation leader.The findings reinforce the existence complementarities among policy instruments and highlight that new avenues of research should explore other policy instruments such as open innovation frameworks.
Keywords: Europe; Idéation, dialogue et maillage; Innovation ouverte; Réservé UdeM

D’un espace de recherche à un espace de production cognitive - Bussières, Denis (La transformation sociale par l'innovation sociale, 2016)
Notre présentation porte sur la relation partenariale qui prend forme entre des praticiens et des chercheurs dans le cadre de recherches impliquant une relation étroite entre ces deux acteurs. Dans la littérature, ce type de recherche se retrouve sous des dénominations différentes : recherche collaborative, recherche-action, recherche partenariale, recherche participative. Ces dénominations impliquent une relation étroite entre chercheurs et praticiens tout au long du processus de recherche. Cette collaboration est concrétisée par le terme de coconstruction des connaissances dont se réclament ces différentes appellations. Nous postulons que cet espace de production cognitive repose sur un dialogue
Keywords: Idéation, dialogue et maillage; Réservé UdeM

Know Your Impact (and in Praise of Better Borrowing) - Mulgan Geoff (Social Innovation: How Societies Find the Power to Change, 2019)
This chapter is about evidence and whether we can, or should, know our impact, the effect we have in the world. It addresses the difficulties as well as the possibilities of evidence for innovators and politicians, civil servants and head teachers, charities and doctors. I also touch on the question at the level of daily life, the moral question of whether we help those around us to be healthier, happier and more prosperous. Knowing our own impacts is, I argue, as much a moral prerogative as the traditional philosophical injunction of knowing ourselves.The enlightenment storyMany of us imbibed from an early age what can be called the enlightenment story. In this story new knowledge is steadily accumulated, mainly in universities and from academic journals. Theories are invented, tested, refuted and then improved. Scepticism helps to refine them and, as Wittgenstein wrote, the child first learns belief and only then learns doubt. You could say that at school we learn knowledge, and then at university we learn to question that knowledge.Belief is strengthened precisely because it has already been knocked down. And so, accumulating knowledge shows that this medicine, that economic policy or this teaching method works and many others don’t. The successful method then spreads, because when you design a better mousetrap the world beats a path to your door. It spreads because people are rational and want to do better and are persuaded by evidence. And so, the world progresses. Light replaces darkness. Effective solutions displace failed ones.It's easy to mock the enlightenment story. The sociologists of science have shown a much messier pattern of change – full of barriers, wilful resistance and peer pressure. But the old enlightenment story contains a good deal of truth and is preferable to the alternatives. Because of intense pressures to act on evidence, and habits of doubt among maintenance staff and engineers, aircraft do not drop out of the sky. Smoking made the slow progress from evidence of harm, through taxes and warnings to full-scale bans, and millions of lives were saved.Experimental methods have been used for many decades.
Keywords: Mesure d'impact; Réservé UdeM

The Evolution of Measures That Matter: How Do We Know If Social Innovation is Working? - Mulgan, Geoff (Social Innovation: How Societies Find the Power to Change, 2019)
In the kingdom of ends everything has either a price or a dignity. What has a price can be replaced by something else as its equivalent; what on the other hand is raised above all price and therefore admits of no equivalent has a dignity.One of the fascinating features of the history of science is how often new ways of seeing preceded new insights. The achromatic-lens microscope in the early 19th century paved the way for germ theory, and X-ray crystallography in the early 20th century played a vital role in the later discovery of the structure of DNA. In the same way flows of data – for example, about how people move around a city, or how blood cells change – can prompt new insights.But how important is measurement to social change? Many people are attracted to metrics and indices of all kinds. But, as my colleague Mark Moore used to warn, ‘do you really think the leaders of the Civil Rights Movement were counting the placards or measuring the decibels of their cries for human rights?’ In social change, as in our own daily lives, measurement often feels inappropriate for the things that matter most.This chapter examines some of the history of social observation as a tool for public policy, social innovation and social change, and I suggest where it might lead in the future. Without some means of measurement, it can be hard to know if a social innovation is good. It may feel good to the beneficiaries – but still be less effective than an alternative. Or it may work well for one group but not another. And, even if it may not be appropriate to measure the passions of movements, once these ideas become part of the mainstream, and are transformed into the cool logic of laws, regulations and programmes, measurements do start to matter a lot, as the Civil Rights Movement discovered.A short history of measurementFor centuries, governments have sought to map and measure social phenomena in order to better exercise control over them. In the modern era these attempts can be traced back to figures like Sir William Petty in England and the cameralists in Prussia.
Keywords: Mesure d'impact; Réservé UdeM

Innovations in Multistakeholder Partnerships for Sustainable Development: Fostering State–University–Community Nexus - Shaban, Abdul; Narnaware, Prashant B. (People-Centered Social Innovation, 2019)
This chapter shows that there is a possibility of fostering an enabling and innovative multistakeholder partnership for creating sustainable impact and transformative change with local communities. It argues that the collaborative efforts among district administration, educational institutions and civil society groups in supporting innovation and entrepreneurship can play an extremely important role in livelihood security and empowerment of marginalized sections. The chapter outlines the transformation of a marginalized and underdeveloped district of India. It presents a background of the district with a focus on farmers’ distress and discusses the mode of organization of elites and marginalized peoples under welfare and neoliberal regimes. The chapter also outlines the impact that state–university engagement on the communities. The neoliberal regime made the elite-based cooperatives ineffective, as they came under mismanagement and overexploitation by those in power. Neoliberal reform introduced a new vulnerability among Indian farmers, especially in certain states, such as Maharashtra.
Keywords: Asie; Réservé UdeM; Rôle des universités

Entrepreneuriat : Théories et pratiques, Applications pour apprendre à entreprendre - Chapitre 5. Entrepreneuriat social - Fayolle, Alain (Entrepreneuriat : Théories et pratiques, Applications pour apprendre à entreprendre, 2017)
Keywords: Entrepreneuriat social; Réservé UdeM

LES MODES D’INNOVATION SOCIALE ET DE GOUVERNANCE - Castro-Spila, Javier; Unceta, Alfonso (La transformation sociale par l'innovation sociale, 2016)
La relation entre l’innovation sociale et la gouvernance n’est pas suffisamment explorée dans la littérature scientifique. Les analyses que l’on trouve sur ce sujet se rapportent principalement à la relation entre l’administration publique, la participation citoyenne, le changement social et les nouvelles formes de gouvernance (Lévesque, 2012 ; Moulaertet al., 2007 ; Novy, Hamme et Leubolt, 2009). Dans ces approches, l’innovation sociale est abordée comme le rapport entre les relations sociales et la gouvernance. Ainsi, cette perspective cherche plutôt à comprendre comment certains groupes sociaux développent leurs capacités sociopolitiques pour garantir leur accès aux ressources qui permettent de répondre

Philanthropy and Innovation - Dodgson, Mark; Gann, David (Philanthropy, Innovation and Entrepreneurship: An Introduction, 2020)
This chapter examines the close relationships between philanthropy and innovation. A case study of philanthropy improving eyesight in Africa is provided. The crucial impact of philanthropy on science and universities is discussed. A case study of how philanthropy fundamentally changed Queensland University is provided. The intimate relationship between philanthropy and the arts is explored. A case study is provided of the impact of philanthropy on a major arts institution. The connections between philanthropy and social and humanitarian innovation is described.
Keywords: Australie; Réservé UdeM

Social Entrepreneurship in an Era of Disruption: Converging Social Change and Sustainability Through Big Data Analysis in a Post-COVID World - Nag, Manmeet Bali (Entrepreneurship and Big Data, 2021)
The world is witnessing an unprecedented disruption due to the COVID-19 pandemic in almost all spheres of socio-economic activity. This black swan moment is unprecedented since the advent of the Industrial Revolution. Simultaneously, there is a shift towards effective use of data and technology. There is an exponential increase in the quantum of data collected and has subsequently necessitated a paradigm shift in the functioning of Industry 4.0. Data intelligence, data science, artificial intelligence, machine learning, and deep assimilation of nuanced knowledge revolutionize business and society worldwide. This heralds a potential transition towards data-intensive economies, governments, industrial and social sectors. The accelerated pace of data processing, data intelligence, and analytics encompasses business intelligence, data sciences and machine learning. The spectrum of such upheavals and associated technological transitions is a watershed moment and impacts business and social transformations. In the paper on the role of data in the social realm (Technology as a catalyst for sustainable social business: Advancing the research agenda, 2019). Ashraf et al. opine that “Despite its immense potentials as a sustainable and innovative means to solve specific social problems, the basic concept of the social business model remains unclear to many”. In recent times there has been an inconsistent approach towards social business research. Subsequently, the contemporary business scenario is yet to optimally capitalize on the advantages of the Social Business concept and address the divergent socio-economic and ecological issues worldwide, with profits intact. This should in no way dilute profit maximization for optimizing socio-economic benefits for value creation and sustainability. “Although the social enterprise is often considered to have positive future potential, it is currently underdeveloped” (Bell, 2003). Therefore, social entrepreneurship should generate and ensure nuanced and effective innovations, addressing underserved needs. In contemporary times, tools harnessing Big Data are becoming widely applied, leading to a huge reservoir of untapped diverse data. This subsequently creates an immense opportunity to accelerate the use of Big Data towards social good and sustainability. Though this is a recent trend, it indeed holds promise in the post-COVID world that would be privy to unprecedented socio-economic upheavals and an increased need to address issues of humankind for greater global welfare. In the recent past, diverse data sets have created large-scale solutions in diverse spheres ranging from weather forecasts to airline tickets. Insightful correlations and Big Data go hand in hand and hold the key to several complicated pressing social issues. Therefore, a new crop of social entrepreneurs in public health, social welfare, and humanitarian relief would surely emerge by default. Therefore, it is all the more relevant to make sense of a deluge of Big Data towards alleviating a disease, ecological imbalance, war, and most importantly, the patterns to cope with the disease and its aftermath. This chapter proposes anticipating and predicting the immense possibilities of optimizing Big Data and digitization as key critical drivers of empirical simulation and troubleshooting. Good governance, inclusive society, elimination of corruption, and streamlining policy measures would emerge as default collectives of such social entrepreneurial ventures. The chapter would draw inferences from such models of socially inclined data analytics by data scientists, leading to relevant social models of significance. Implications of the chapter would be to assuage the fault lines, draw inferences from the past, and delve into the plausibility and relevance of Big Data to replicate and innovate socially relevant models to map bigger social issues. This, of course, should have embedded benchmarks of equality, ethics, and empowerment while processing Big Data for a greater social good in a post-COVID world gaping at us.
Keywords: Big Data; Entrepreneuriat; Réservé UdeM; Social entrepreneurship

Social Entrepreneurship - Sumbly, Sangeeta (Entrepreneurship and Big Data, 2021)
Social entrepreneurship is today an imperative across the world. The scarcity of resources, the needs of the growing population, and the growing burden on the environment have made people realize a need for organizations that can be profitable while bringing positive change in society and the environment. Sustainable, out-of-the-box solutions are required for solving social challenges. The onus of providing these solutions are often taken by aspiring entrepreneurs, who see opportunity in the challenges and are willing to take risks to create innovative and effective solutions for society’s benefit. The chapter elucidates the meaning of social entrepreneurship, the difference between commercial and social entrepreneurship, the models of social enterprises in practice, and the recommended methodology to evaluate social impact. The chapter features international case studies (through secondary research) and cases about social entrepreneurs who have dramatically improved the lives of people while being financially sustainable – an organization like SELCO Solar Lights Private Ltd, ARMAAN, Yellow Leaf and Arvind Eye Hospital, and many others have provided solutions for the economically weaker section of society. Many of these new-age social entrepreneurs use Big Data and artificial intelligence to ensure that their initiatives create greater social change. Some of these initiatives are highlighted in the chapter.
Keywords: Big Data; Entrepreneuriat; Réservé UdeM; Social entrepreneurship; social

Toward the Practice of Social Innovation for the Common Good: An Integration of “Teaching-Research-Service” - Han, I.; Hou, Sheng-Tsung (Social Innovation and Business in Taiwan, 2016)
“Many suppliers and users of social research are dissatisfied, the former because they are not listened to, the latter because they do not hear much they want to listen to” (Lindblom & Cohen, 1979: 1). As mentioned in Chapter 1 of this book, the recent events of global financial crisis and a series of Occupy Wall Street protests have raised reflections of business management education on MBA trainings. The question of whether management research and education can be a facilitator toward events that would eventually destroy the world economy or a facilitator toward achieving social value and human glory has been raised with those reflections. MBA graduates should not be used as profiting tools for big corporations anymore. Moreover, the separation between management theory and industry practice has, for a long time, caused a dilemma with regard to the difficulties inherent in dialogue between academia and industry. There have been urgent calls to embody management research into applicable industry knowledge in order to minimize the gap in between the two (Anderson, Herriot, & Hodgkinson, 2001; Rynes, Bartunek, & Daft, 2001; Van de Yen & Johnson, 2006).
Keywords: Asie; Réservé UdeM